PENINGKATAN PENGETAHUAN PETANI ANGGOTA GAPOKTANHUT JAYA MAKMUR DESA CILIMUS, PROVINSI LAMPUNG TENTANG PEMELIHARAAN POHON - INDRIYANTO, INDRIYANTO; SURNAYANTI, SURNAYANTI; ASMARAHMAN, CENG; TSANI, MACHYA KARTIKA; DURYAT, DURYAT; DAMAYANTI, INGGAR; SANTOSO, TRIO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
The knowledge of forest farmers who are members of Gapoktanhut Jaya Makmur regarding tree maintenance is still low, so they have never carried out maintenance on the trees which planted at the cultivated area in the Wan Abdul Rachman Grand Forest Park. Community service was carried out to increase forest farmers' knowledge about aspects of tree maintenance. The methods used were lectures, discussions, as well as tree maintenance practices. Changes knowledge were evaluated through pre test and post test with questionnaires. The results showed that farmers' knowledge regarding the importance of tree maintenance increased by 12.4 value, farmers' knowledge regarding how to control weeds increased by 11.2 value, farmers' knowledge about how to fertilize trees increased by 12.2 value, farmers' knowledge about how to control pests and diseases increased by 13.0 value, and farmers' knowledge of how to control parasitic plants increased by 13.0 value. This increase in knowledge was experienced by each farmer participating in the community service with an average increase in value of 12.4 from an average pre test value of 58.5 to 70.9. It was concluded that the community service had been carried out succeeded in increasing forest farmers' knowledge about how to care for trees. With the increased knowledge of forest farmers, it is hoped that they will be willing and able to properly and continuously maintain trees that have been planted in their cultivated areas so that the trees can live healthy and productive lives. ABSTRAKPengetahuan petani hutan anggota Gapoktanhut Jaya Makmur tentang pemeliharaan pohon masih rendah sehingga mereka belum pernah melakukan pemeliharaan pohon yang ditanam di areal garapan dalam Taman Hutan Raya Wan Abdul Rachman. Pengabdian kepada masyarakat dilakukan untuk meningkatkan pengetahuan petani hutan tentang aspek pemeliharaan pohon. Metode yang digunakan adalah ceramah dan diskusi, serta praktik pemeliharaan pohon. Perubahan pengetahuan petani dievaluasi menggunakan kuesioner pada awal dan akhir kegiatan pengabdian. Hasil pengabdian adalah pengetahuan petani mengenai pentingnya pemeliharaan pohon meningkat nilai sebesar 12,4, pengetahuan petani mengenai cara pengendalian gulma meningkat nilai sebesar 11,2, pengetahuan petani mengenai cara pemupukan pohon meningkat nilai sebesar 12,2, pengetahuan petani mengenai cara pengendalian hama dan penyakit meningkat nilai sebesar 13,0, dan pengetahuan petani mengenai cara pengendalian tumbuhan parasit meningkat nilai sebesar 13,0. Peningkatan pengetahuan tersebut dialami oleh setiap petani peserta pengabdian dengan rata-rata peningkatan nilai sebesar 12,4 dari rata-rata nilai evaluasi awal sebesar 58,5 menjadi 70,9. Disimpulkan bahwa pengabdian kepada masyarakat yang telah dilakukan berhasil meningkatkan pengetahuan petani hutan mengenai cara pemeliharaan pohon. Meningkatnya pengetahuan petani hutan tersebut diharapkan mereka mau dan mampu melakukan pemeliharaan pohon yang telah ditanam di areal garapannya secara benar dan kontinu agar pohon-pohon bisa hidup sehat dan produktif.